2004
DOI: 10.1074/jbc.m408472200
|View full text |Cite
|
Sign up to set email alerts
|

A Naturally Occurring Mutation of the Opsin Gene (T4R) in Dogs Affects Glycosylation and Stability of the G Protein-coupled Receptor

Abstract: Rho (rhodopsin; opsin plus 11-cis-retinal) is a prototypical G protein-coupled receptor responsible for the capture of a photon in retinal photoreceptor cells. A large number of mutations in the opsin gene associated with autosomal dominant retinitis pigmentosa have been identified. The naturally occurring T4R opsin mutation in the English mastiff dog leads to a progressive retinal degeneration that closely resembles human retinitis pigmentosa caused by the T4K mutation in the opsin gene. Using genetic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 71 publications
2
55
1
Order By: Relevance
“…Although the introduction of a positive charge may destabilize this region in the case of T4K, as is proposed for the T4R dog (Zhu et al, 2004), our results obtained from the T4N mutant suggest that the underlying reason is loss of the ␤-sheet configuration.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the introduction of a positive charge may destabilize this region in the case of T4K, as is proposed for the T4R dog (Zhu et al, 2004), our results obtained from the T4N mutant suggest that the underlying reason is loss of the ␤-sheet configuration.…”
Section: Discussionmentioning
confidence: 54%
“…Although a mouse model expressing human T17M rhodopsin exists (Li et al, 1998), localization of the mutant rhodopsin was not determined. In a naturally occurring dog model of RP, mutant T4R rhodopsin localizes to the ROS (Zhu et al, 2004). Our results indicate that nonglycosylated rhodopsin (N2S/N15S rhodopsin) was capable of targeting to and inserting into ROS disk membranes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Several studies have indicated that loss of GPCR glycosylation can lead to improper folding and targeting, resulting in decreased function and compromised structure and stability (11). Loss of either N-terminal glycosylation site (Asn-2 or Asn-15) of rhodopsin is sufficient to cause loss of signal transduction despite no apparent change in localization or folding (21,22). Additionally, mutating out the glycosylation site of a mouse OR (mOR-EG) was found to abolish its ability to localize to the membrane (10), indicating that this modification may be necessary for OR function.…”
Section: Discussionmentioning
confidence: 99%
“…We genetically eliminated the retinoid cycle, the process that regenerates the light-sensitive chromophore 11-cis-retinal (51,52). In contrast to adRP-causing opsin gene mutations P23H (29) and T4R (18,53), the E150K mutant opsin appears more stable under such conditions, inducing a milder retinal disease phenotype than these counterparts. This could be attributed to the profound oligomerization of opsin versus rhodopsin that could preferentially benefit the E150K mutant ROS.…”
Section: Figurementioning
confidence: 99%